Resolving issues with environmental impact assessment of marine renewable energy installations - Maclean, Ilya M. D.; Inger, Richard; Benson, David; Booth, Cormac G.; Embling, Clare B.; Grecian, W. James; Heymans, Johanna J.; Plummer, Kate E.; Shackshaft, Michael; Sparling, Carol E.; Wilson, Ben; Wright, Lucy J.; et al. (Frontiers in Marine Science, 2014)
Growing concerns about climate change and energy security have fuelled a rapid increase in the development of offshore and marine renewable energy installations (OMREIs). The potential ecological consequences of increased use of these devices emphasises the need for high quality environmental impact assessment (EIA). We demonstrate that these processes are hampered severely, primarily because legislation does not ensure that the significance of impacts and cumulative effects are properly assessed. We highlight why the regulatory framework leads to conceptual ambiguities and propose changes which, for the most part, do not require major adjustments to standard practice. We emphasise the importance of determining the degree of confidence in impacts to permit the likelihood as well as magnitude of impacts to be quantified and propose ways in which assessment of population-level impacts could be incorporated into the EIA process. Overall, however, we argue that, instead of trying to ascertain which particular developments are responsible for tipping an already heavily degraded marine environment into an undesirable state, emphasis should be placed on better strategic assessment.